2009
DOI: 10.1258/td.2008.080178
|View full text |Cite
|
Sign up to set email alerts
|

Barriers experienced by parents of children with clubfoot deformity attending specialised clinics in Uganda

Abstract: Clubfoot is a congenital structural impairment that, if untreated or inadequately treated, leads to deformity. Effective management is dependent on the compliance of parents to the treatment for clubfoot. A cross-sectional descriptive survey using a questionnaire identified the barriers parents encounter in bringing their children for treatment during the plaster-casting stage of managing clubfoot at the Talipes Clinics at Mbarara Regional Hospital and Mulago Hospital in Uganda. A total of 167 parents particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 9 publications
4
32
0
Order By: Relevance
“…The feminine gender dominance in this study concurs with the observation made in a study conducted in Uganda on parents/caregivers who took their children at an outpatient treatment clinic for clubfoot management (Kazibwe, 2006). A similar study by Kadzin and Wassell (1999) in USA found that out of 200 parents/caregivers, who took part in a study on barriers to treatment participation reported that majority of them were mothers or female relatives.…”
supporting
confidence: 88%
“…The feminine gender dominance in this study concurs with the observation made in a study conducted in Uganda on parents/caregivers who took their children at an outpatient treatment clinic for clubfoot management (Kazibwe, 2006). A similar study by Kadzin and Wassell (1999) in USA found that out of 200 parents/caregivers, who took part in a study on barriers to treatment participation reported that majority of them were mothers or female relatives.…”
supporting
confidence: 88%
“…[ 9 ] Even when treatment and rehabilitation services are available, there is evidence from LMIC settings that uptake of referrals to these services can be low among children with different impairments. [ 10 14 ] However empirical evidence on the uptake of and barriers to referrals for ear and hearing services among children is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of factors have been identified that act as barriers to service delivery including financial constraints of the service , a related lack of resources and a lack of training for physicians . The majority of patients with clubfoot in LMICs may not come forward for treatment, and many of those who do start treatment do not continue with it . Understanding factors that affect access and adherence to clubfoot treatment may help to inform ways of encouraging uptake and engagement with services that have the potential to improve a child's well‐being and ability to participate in a range of everyday activities.…”
Section: Introductionmentioning
confidence: 99%
“…Once these are understood, services can be developed to meet their needs most appropriately. Qualitative studies are particularly adept at providing information about experiences of health and healthcare, and a number of qualitative studies have identified factors that affect patient access to clubfoot treatment in LMICs and suggested community‐level interventions to address them . Increasingly, it is thought that synthesis of previous qualitative work can deliver results that are of relevance to multiple contexts .…”
Section: Introductionmentioning
confidence: 99%